A first-in-human study to investigate the safety, tolerability, pharmacokinetics, and pharmacodynamics of KM-819 (FAS-associated factor 1 inhibitor), a drug for Parkinson’s disease, in healthy volunteers - Shin W; Lim KS; Kim MK; Kim HS; Hong J; Jhee S; Kim J; Yoo S; Chung YT; Lee JM; Cho DY (Drug Design, Development and Therapy, 2019)
Wonsuk Shin,1 Kyoung Soo Lim,1 Min-Kyoung Kim,1 Hyun Sook Kim,2 Jihwa Hong,3 Stanford Jhee,3 Joseph Kim,3 Sungeun Yoo,4 Yeon-Tae Chung,4 Jae Moon Lee,4 Doo-Yeoun Cho1 1Department of Clinical Pharmacology and Therapeutics, CHA Bundang Medical Center, CHA University School of Medicine, Seongnam, Republic of Korea; 2Department of Neurology, CHA Bundang Medical Center, CHA University School of Medicine, Seongnam, Republic of Korea; 3Department of Scientific Affairs, PAREXEL International, Waltham, MA, USA; 4Kainos Medicine Inc., Seongnam, Republic of Korea Background: KM-819 is a novel FAS-associated factor 1 (FAF1) inhibitor, and a neuroprotective agent, under clinical development for the treatment of Parkinson’s disease as a disease-modifying drug.Methods: This first-in-human, single and multiple ascending dose study investigated the safety, tolerability, pharmacokinetics, and pharmacodynamics of KM-819 in healthy volunteers. Additionally, the effect of age on safety and pharmacokinetics were assessed. The starting dose was determined considering the no observed adverse effect level based on preclinical studies, and the dose escalations in subsequent cohorts were decided based on safety, tolerability, and pharmacokinetic data from previous dose cohorts.Results: After a single dose, the KM-819 plasma exposure showed a less than dose-proportional increase across a dose range of 10–400 mg. After repeated dosing, KM-819 plasma exposure increased in an approximately dose-proportional manner across the evaluated dose range (30–400 mg once daily for 7 days). The mean elimination half-life was 1.8 to 4.8 h with the lower KM-819 doses (≤30 mg), which increased to around 9 h with the higher doses (100–400 mg). When administered to the elderly population, KM-819 plasma exposure increased to 102% after a 200 mg once-daily dosing for 7 days. No clear treatment-related effects on the estimated pharmacodynamic variables were observed. Single or multiple doses of KM-819 were generally well tolerated. Conclusion: The data from this study can be used to guide rational drug dosing and choose therapeutic regimens in subsequent clinical studies. Keywords: first-in-human, KM-819, pharmacokinetics, pharmacodynamics, safety